2018
DOI: 10.3892/ijmm.2018.3863
|View full text |Cite
|
Sign up to set email alerts
|

Eleutheroside B1 mediates its anti-influenza activity through POLR2A and N-glycosylation

Abstract: Influenza viruses represent a serious threat to human health. Although our research group has previously demonstrated the antiviral and anti-inflammatory activities of eleutheroside B1, a detailed explanation of the mechanism by which it is effective against the influenza virus remains to be elucidated. In the present study, the transcriptomic responses of influenza A virus-infected lung epithelial cells (A549) treated with eleutheroside B1 were investigated using high-throughput RNA sequencing, and potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…This combination was tested in controlled clinical trials for the treatment of common cold and influenza‐associated uncomplicated upper respiratory infections as well as for the prevention of common colds 421–424 . The studies confirmed the safety and superior efficacy of this combination regimen as compared with monodrug therapy, 425 presumably because of its antiviral effects, 426–432 effects on innate and adaptive immunity, 433–437 and anti‐inflammatory, antioxidant, and detoxifying effects 438–441 of both adaptogenic plants as well as due to their synery 25 . It should be noted that the postmarketing pharmacovigilance assessment of Kan Jang showed a high benefit–risk ratio: one adverse event in about 100,000 patients was recorded for the 23‐year period from the adverse event reports (concerning mainly allergic reactions) to the Swedish and Danish medical product agencies.…”
Section: Current and Prospective Use Of Adaptogens In Stress‐induced mentioning
confidence: 84%
“…This combination was tested in controlled clinical trials for the treatment of common cold and influenza‐associated uncomplicated upper respiratory infections as well as for the prevention of common colds 421–424 . The studies confirmed the safety and superior efficacy of this combination regimen as compared with monodrug therapy, 425 presumably because of its antiviral effects, 426–432 effects on innate and adaptive immunity, 433–437 and anti‐inflammatory, antioxidant, and detoxifying effects 438–441 of both adaptogenic plants as well as due to their synery 25 . It should be noted that the postmarketing pharmacovigilance assessment of Kan Jang showed a high benefit–risk ratio: one adverse event in about 100,000 patients was recorded for the 23‐year period from the adverse event reports (concerning mainly allergic reactions) to the Swedish and Danish medical product agencies.…”
Section: Current and Prospective Use Of Adaptogens In Stress‐induced mentioning
confidence: 84%
“…The formation of subnuclear paraspeckle structures depend on transcription and RNA polymerase II in response to stress or cellular metabolic changes (45). The mRNA data analysis also indicated that the effect of eleutheroside B1 on RNA polymerase and RNA synthesis was required for the anti-influenza activity (46). Previous studies have proven that NEAT1 is a crucial innate immune molecule with dual functions (44).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, another limitation is that ncRNA expression was not examined at different time points. Previous research (46) has often selected 24 h after infection for RNA-seq; therefore, this time point was used for detection in this study. In the future, the authors aim to perform further studies using different time points.…”
Section: Discussionmentioning
confidence: 99%
“…EP300 and CREBBP target a significant number of proteins for acetylation, including cytosolic proteins involved in essential metabolic processes 21 . POLR2A is a key virus polymerase-interacting protein and is required for viral replication and transcriptional activity 22 . Cell division cycle 20 (CDC20) encodes a regulatory protein and plays important roles in tumorigenesis 23 .…”
Section: Discussionmentioning
confidence: 99%